A new species of Notonyx A. Milne-Edwards, 1873 (Crustacea: Decapoda: Brachyura: Goneplacidae) from Indonesia - Ng, Peter K. L.; Clark, Paul F. (Zootaxa, 2008)
A new species of Notonyx A. Milne-Edwards, 1873 (Crustacea: Brachyura: Goneplacidae) is described from the Lesser Sunda Islands, Indonesia. It differs from known congeners by possessing a relatively broader carapace and distinctive male first gonopod. The affinities of the new species with the superficially similar N. nitidus A. Milne-Edwards, 1873, and N. gigacarcinicus Clark & Ng, 2005, are discussed.